Diagnóstico de los transformadores de potencia de la empresa minero industrial Cerro Matoso S.A, mediante el análisis del aceite dieléctrico (2020)
By carrying out this project, the aim is to carry out a diagnosis on the state of operation of the power transformers of the Cerro Matoso S.A industrial mining company; based on the existing information, delivered by the ABB and Transequipos laboratories, associated with electrical predictive maintenance in the plant maintenance business unit, updated until 2018. In the process, threats were identified through the analysis of dielectric oil tests, to optimize the processes of interpretation of the condition of the equipment's condition, allowing to guarantee correct decision-making and reduce environmental, legal, and labor risks. And economical that an electrical failure would bring. The work is carried out in three phases: 1) Collection of information, 2) Data analysis, 3) Issue of diagnosis and maintenance recommendations. The analysis of the reports of the transformers T01, T02, T03, T04, T20, T21, T22, T150, T151, T152, T155 and T156, taking into account the parameters established in the IEEEC57-106 2015 standards for ADFQ and IEEE C57 -104 2008 for DGA. It allowed to conclude that the behavior of the transformers in the installed electrical base, through the analysis of the dielectric oil tests carried out, show that in general terms, the equipment under study is in good condition, except for the T150 and T152 transformers, that require corrective maintenance, since the study of Dissolved Gases shows us that there is a high level of oil decomposition, which translates into transformer failures, while the others only require periodic annual maintenance.